Perlindungan Hukum Peserta Event Lari Dalam Program Jaminan Kecelakaan Kerja - Hermawati, Galuh Dwi; Rosando, Abraham Ferry (Journal Evidence Of Law, 2025)
As living beings, survival is a basic human instinct. An effective approach to achieving this goal is by prioritizing physical well-being. Engaging in regular exercise is among the most reliable methods to preserve overall health and enhance physical fitness. Among the various types of sports, running is the most popular physical activity. Some factors that make running popular are because it is economical and can be done anywhere. There are many reasons why people choose to run, from maintaining physical health, as a recreational activity, to as a permanent profession that is generally done by athletes. The type of running that is most in demand by the public is long-distance running. Legal protection for participants in running events in the Work Accident Insurance program is an important effort to provide safety and security for participants who take part in sports activities. The Work Accident Insurance program managed by Social Security Administering Body for Employment, especially for Non-Wage Recipient participants, offers safeguards against the possibility of accidents that might happen during the activity. This research seeks to examine the effectiveness of legal protections provided by the program in ensuring the safety of participants during running events, specifically in mitigating risks of injuries or accidents.